DECLARATORY LAWSUIT IN CIVIL LAW PROCEDURE IN BOSNIA AND HERZEGOVINA (IUS LAW Journal, 2025)
The focus of this article is the position of declaratory lawsuits in Civil law procedure in thelegislation of Bosnia and Herzegovina. Compared to other types of lawsuits (condemnatory andconstitutive), a declaratory lawsuit is primarily aimed at obtainin g a declaration by a court of theexistence or non existence of certain legal relationships or rights and the declaration of authenticityof some private or public legal document as well as the determination of a violation of personalrights. Further uses of declarative lawsuit can be, as foreseen by specific legal provisions, adeclaration of the existence or non existence of certain facts on which the fulfilment of other rightsmay depend. The existence of legal interest is one of the procedural elements of a declaratorylawsuit. The use of declaratory lawsuits has proven itself to be a more adequate way of legalprotection in certain cases, especially when the use of other types of lawsuits is unavailable forlegal or factual reasons. Even though the use of declaratory lawsuits has expanded, the removal ofcertain restrictions on the right use of declaratory lawsuits could be recommended de lege ferendain order to facilitate the maximization of the potential of the declaratory lawsuit in civil legalproceedings.
Keywords: Civil Law, Lawsuit, Declaratory Lawsuit, Civil Procedure